Study of Tannery Phase Diagram of Rotenone Derris elliptica (Fabales: Fabaceae): A Novel Approach of Insecticide Formulation - Ahmad, S.N.B.; Islam, M.T.; Abdullah, D.K.; Omar, D. (Asian Journal of Chemistry, 2013)
The present study was conducted for evaluating the tannery phase diagram of microemulsion formulation of rotenone. In this paper, oil-in-water microemulsions were obtained by the titration method through ternary phase diagram study. The widest oil-in-water microemulsion region (48 % isotropic area) in phase diagram system was obtained in Tween 20/Agnique BL 7001/water system compared with others, while the narrowest oil-in-water microemulsion region (6 % isotropic area) was obtained in Agnique PG 9116/Edenor ME/water system. This novel approach for insecticide formulation of rotenone might be useful for the control of insect. This study will provide the maximum utilization of botanical insecticide concerning environmental friendly strategy.